Karakterisasi Hama Baru Spodoptera Frugiperda Pada Tanaman Jagung (Zea mays L.) Di Lombok Barat - Juwanda, Erwin; Supeno, Bambang; Haryanto, Hery; Hari Aditia Pratama, Muhammad (Master’s Program in Biology, Faculty of Mathematics and Natural Sciences, University of Mataram, 2025)
Maize (Zea mays L.) is the main food crop in Indonesia after rice, but is vulnerable to attack by plant pests (OPT), including Spodoptera frugiperda, an invasive insect that attacks corn plants. This research aims to observe the population, level of attack and characteristics of the pest of S. frugiperda in West Lombok Regency. Based on observations, the eggs of this pest are brownish white, round in shape, and have an average size of 0.33 mm × 0.47 mm. The male pupa is reddish brown with dimensions of 14.25 mm × 4.32 mm, while the female pupa is larger, namely 17.53 mm × 5.13 mm. Larvae are found in various instars (2-6) with sizes from 1.53 mm to 35.16 mm, and colors varying from light green to dark brown. Male imagos are smaller than females, with a length of 12.45 mm and a wingspan of 27.73 mm, while female imagos have a size of 14.38 mm and a wingspan of 31.47 mm. The highest population was found at location 3 with 123 larvae, while the lowest population was at location 13 with 1 larva. The highest attack rate occurred at location 7 (50%) and the lowest at location 11 (5%). The observation method includes assessing the level of damage based on the attack intensity score (0–4). This research proposes further studies to understand the distribution and control mechanisms of S. frugiperda in order to minimize its impact on corn cultivation, especially in Nusa Tenggara Barat, Indonesia.